تعلّيم الإنشاء في قسم اللغة العربية بالجامعة التهذيب الإسلامية جومبانج - Akbar, Dhoyfun; Istiqomah, Ismi (Al-Fakkaar, 2025)
This study aims to analyze the problems in teaching insya’ (composition) to students of Arabic Language Education. It was found that the effectiveness of teaching remains low due to challenges related to lecturers, students, materials, methods, and evaluation, which focus solely on grammar. This research employs a qualitative approach with an evaluative type, utilizing interviews, observations, and documentation. The results show weaknesses in planning, material selection, and a lack of attention to content, as well as variations in students’ competencies and interests. The researcher proposes solutions such as gradual instruction, comprehensive evaluation, and the development of other language skills. Students’ learning outcomes are influenced by their language proficiency and learning practices.